2004
DOI: 10.1007/s10008-003-0488-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen transport in La0.6Sr0.4Co1−y Fe y O3−δ

Abstract: The surface exchange coefficient and chemical diffusion coefficient of oxygen for the perovskites La 0.6 Sr 0.4 Co 1)y Fe y O 3)d (y=0.2, 0.5 and 0.8) were measured using the conductivity relaxation technique. Measurements were performed between 600 and 800 °C in an oxygen partial pressure range between 10 )4 and 1 bar. Both transport coefficients decrease markedly with decreasing oxygen partial pressure below about 10 )2 bar at all temperatures. This is attributed to ordering of oxygen vacancies. Implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
178
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(212 citation statements)
references
References 17 publications
21
178
3
Order By: Relevance
“…Many publications have assessed the D and k values of MIEC materials, most commonly by; electrical conductivity relaxation (ECR) measurements for dense bulks [4][5][6][7][8] and temperature for LSCF cathodes. 17 Here it should be pointed out that the well-known ALS model can only be applied if the measured impedance shows a Gerischer impedance, which indicates that the surface-exchange and the oxygen bulk diffusion are strongly coupled.…”
Section: -3mentioning
confidence: 99%
“…Many publications have assessed the D and k values of MIEC materials, most commonly by; electrical conductivity relaxation (ECR) measurements for dense bulks [4][5][6][7][8] and temperature for LSCF cathodes. 17 Here it should be pointed out that the well-known ALS model can only be applied if the measured impedance shows a Gerischer impedance, which indicates that the surface-exchange and the oxygen bulk diffusion are strongly coupled.…”
Section: -3mentioning
confidence: 99%
“…However, when CO 2 (50 ml/min) was introduced, the flux suddenly dropped to 7.2×10 -7 mol/cm 2 /s, followed by a decrease to almost zero after 57 hours of CO 2 exposure at the sweep side of the membrane. For SCFTa, it took almost 30 hours to achieve a steady oxygen permeation flux in helium, which has also been found by Zhu and Yi in their work [25,26]. This could be due to readjusting of the lattice structure from the as-prepared state to a steady state under permeation conditions or to a reduction of the initial surface oxygen desorption rate.…”
Section: Methodssupporting
confidence: 65%
“…Chen et al [26] have also found that ~4 mol% Zr-doping at the B-site can stabilize SCF to ~700 o C in a For membranes, to be used in the 4-end mode, one of the options is to use CO 2, which is known as an acid gas, as the sweep gas. As most of the MIEC oxides contain alkaline-earth elements (Ca, Sr or Ba) a carbonation reaction occurs when these membranes are exposed to a CO 2 -containing atmosphere.…”
Section: State Of the Art Membranes For Oxy-fuel Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Electrochemical measurements on LSCF-6428, including conductivity relaxation, 3,5 coulometry, 4,6 and impedance techniques 2,7,8 have underscored the importance of bulk oxygen vacancies in governing rates of O 2 reduction and evolution. However, a clear understanding of how these vacancies contribute to the mechanism and rate-limiting step(s) of O 2 exchange remains elusive.…”
mentioning
confidence: 99%